2010
DOI: 10.1242/jeb.040881
|View full text |Cite
|
Sign up to set email alerts
|

Green fluorescent protein regulation in the coral Acropora yongei during photoacclimation

Abstract: ). Green fluorescence increased ~1.9 times in high light corals and decreased ~1.9 times in low light corals compared with medium light corals. GFP concentration and green fluorescence intensity were significantly correlated. Typical photoacclimation responses in the dinoflagellates were observed including changes in density, photosynthetic pigment concentration and photosynthetic efficiency. Although fluorescent proteins are ubiquitous and abundant in scleractinian corals, their functions remain ambiguous. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(124 citation statements)
references
References 71 publications
(106 reference statements)
4
118
0
Order By: Relevance
“…In the greenpigmented tentacles of G. fascicularis, GFP is located in the epidermis above the zooxanthellae and the content of GFP was higher on the sunlit side of the tentacles than on the shaded side. This is consistent with the report by Roth et al (2010) …”
Section: Discussionsupporting
confidence: 94%
“…In the greenpigmented tentacles of G. fascicularis, GFP is located in the epidermis above the zooxanthellae and the content of GFP was higher on the sunlit side of the tentacles than on the shaded side. This is consistent with the report by Roth et al (2010) …”
Section: Discussionsupporting
confidence: 94%
“…In addition, there are corals that express a very weak GFP signal if any, (e.g., Porites sp.) (Roth et al, 2010) whose identification was only possible by their texture and shape in the fluorescence images. Light intensity is known to modulate pigmentation in corals of the species Acroporidae, Merulinidae, and Pocilloporidae (D'Angelo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that corals can also vary the amount of FPs within their tissues in response to changes in environmental and physiological conditions (D'Angelo et al 2008, Roth et al 2010. However, in shallow Caribbean corals (3−30 m), there is no correlation between depth and GFP abundance in Montastrea cavernosa and M. faveolata (Mazel et al 2003).…”
Section: Coral Fluorescence In the Mesophotic Zonementioning
confidence: 96%
“…While reef-building corals have the capacity to produce significant quantities of FPs (Leutenegger et al 2007), the function of FPs is unknown. As a result of ambiguous data which may be caused by the diversity of FPs and corals, hypothesized roles for the function of FPs include photoprotection (Salih et al 2000, Roth et al 2010, Smith et al 2013, antioxidant activity (Mazel et al 2003, Bou-Abdallah et al 2006, Palmer et al 2009a), photosynthesis enhancement (Salih et al 2000), Symbiodinium regulation (Field et al 2006), part of an immune response (Palmer et al 2009b, D'Angelo et al 2012, camouflage (Matz et al 2006b), maintenance of color diversity (Dove et al 2001), and attraction of free-living Symbiodinium (Hollingsworth et al 2004). It is possible that different FPs could have different roles, particularly in distinct environments such as shallow or mesophotic habitats.…”
Section: Introductionmentioning
confidence: 99%